Pain relief for strabismus surgery in children: a randomised controlled study of the use of preoperative sub-Tenon levobupivacaine. Issue 3 (3rd December 2008) - Morris, B; Watts, P; Zatman, T; Absolom, M; Haider, S; Hall, J
Abstract : Aims: To compare the postoperative pain scores in children undergoing squint surgery administered with preoperative sub-Tenon levobupivacaine for postoperative pain relief versus controls. Methods: A prospective randomised controlled clinical trial was performed. Children aged 1–16 years undergoing strabismus surgery were recruited. The test group received sub-Tenon levobupivacaine preoperatively and topical anaesthetic eye-drops at the end of the procedure. The control group received topical anaesthetic eye-drops only at the end of surgery. Pain scores were recorded at 30 min, 2, 4, 6 and 24 h postoperatively using the Wong–Baker Pain or FLACC (face, legs, arms, cry, consolability) assessment score. The principal outcome measured was the pain score at each time interval for both groups. Results: 27 patients received sub-Tenon levobupivacaine, and there were 27 age- and sex-matched controls. The pain score in the test group was not lower than that of the control group (p = 0.22 at 30 min, p = 0.37 at 2 h). Conclusions: Sub-Tenon levobupivacaine, which is widely used for postoperative pain relief in paediatric strabismus surgery, was not effective when administered preoperatively in this cohort.